A cellular metastructure incorporating coupled negative thermal expansion and negative Poisson's ratio. (1st October 2018) - Wei, Kai; Peng, Yong; Qu, Zhaoliang; Pei, Yongmao; Fang, Daining
Highlights: A metastructure is devised to obtain tailorable thermal expansion and tunable Poisson's ratio. Analytical expressions for thermal expansion and Poisson's ratio are established and numerically validated. The metastructure can give paired negative thermal expansion and negative Poisson's ratio. Tailorable thermal expansion and Poisson's ratio are highly coupled with common parameters. Abstract: Current reported cellular metastructures can either achieve only tailorable thermal expansion or obtain only tunable Poisson's ratio. By contrast, here, we develop a kind of lightweight cellular metastructure which incorporates coupled tailorable thermal expansion and tunable Poisson's ratio. That is a wide range of positive, zero and especially negative values of both thermal expansion and Poisson's ratio can be simultaneously obtained. The ranges and constraints of the geometrical parameters are revealed, and the relative densities are only about 2%, indicating excellent lightweight character. Besides, analytical expressions for coefficient of thermal expansion (CTE) and Poisson's ratio (PR) are theoretically established and numerically simulated. Parameter analysis confirms that the range of tailorable CTE can be enhanced through rationally selecting large values of CTE ratio, first geometrical angle and height ratio. By adjusting the second and third geometrical angles, Poisson's ratio also can be tuned to be large negative, near zero and positive values. Particularly, the metastructure can give paired negative CTE and negative PR. Different combinations of paired characteristics including positive CTE + negative PR, positive CTE + positive PR and negative CTE + positive PR are also flexibly available. Moreover, CTE and PR are found to be highly coupled. To simultaneously obtain specific CTE and PR, design parameters should be selected with consideration of the coupling effect. The results here are expected to contribute feasibility to structures with both temperature and mechanical sensitivities.